ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF SERTA IMPLIKASI KEBIJAKAN PEMERINTAH PADA KOMODITAS JAGUNG DI KABUPATEN BENGKAYANG (Jurnal Social Economic of Agriculture, 2016)
The aims of this research are (1) To Analyze the comparative and the competitive advantages of maize in Kabupaten Bengkayang (2) To analyze the impact of the government policy of maize in Kabupaten Bengkayang. The Analyze method use a Policy Analisys Matrix (PAM). The analisys showed that Domestic Resource of Ratio were 0,59 and Private Cost Ratio were 0,81. Both of them are less than one that’s mean the maize had the comparative and competitive advantages. To see the government policy of input can be shown from the Nominal Protection Coefficient on Output (NPCO). To see the government policy of input can been shown from the Nominal Coefficient on Input (NPCI) and factor Transfer. Simultanly the government policy if input and output can be shown from the Effective Protection Coefficient Value (EPC), Profitability Coefficient (PC) and Surplus Ratio to Producer (SRP). The analisys result shown that there is no government policy that have been made to the maize output in Kabupaten Bengkayang, right in buying  price subsidiary or protection of actual buying price. The government policy to maize input has been shown to the farmer side, but the subsidiary input price not profitable enough to increasment and development of maize product in Kabupaten Bengkayang if not followed by output price policy.Keyword : Comparative and Competitive Advantages, Policy Analisys Matrix, Maize